2021
DOI: 10.1186/s12954-021-00460-0
|View full text |Cite|
|
Sign up to set email alerts
|

Individual and structural correlates of willingness for intravenous buprenorphine treatment among people who inject sublingual buprenorphine in France

Abstract: Background Some people do not benefit from oral administration of opioid agonist treatment, and an intravenous (IV) formulation may be more suitable. Our objective was to evaluate the willingness of people who regularly inject sublingual buprenorphine to receive IV buprenorphine as a prescribed treatment, and to examine related correlates. Methods We performed a secondary analysis of data from the cross-sectional study PrebupIV, conducted in France… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…For example, they describe take-home doses as a form of equity and accessibility in their treatment, as the time and expense of getting to the clinic multiple times a day was a major challenge to remain engaged in care, similar to prior research on methadone (22). Prior research indeed indicates that the intensity of iOAT (e.g., multiple daily in-person appointments) is a deterrent for potential clients to want to engage in the program (72,73). Not surprisingly, participants reported that the demanding schedule of appointments made them consider returning to the illicit market, which aligns with previous research shows that clients will return to the illicit market if treatment is not accessible (74).…”
Section: Discussionmentioning
confidence: 76%
“…For example, they describe take-home doses as a form of equity and accessibility in their treatment, as the time and expense of getting to the clinic multiple times a day was a major challenge to remain engaged in care, similar to prior research on methadone (22). Prior research indeed indicates that the intensity of iOAT (e.g., multiple daily in-person appointments) is a deterrent for potential clients to want to engage in the program (72,73). Not surprisingly, participants reported that the demanding schedule of appointments made them consider returning to the illicit market, which aligns with previous research shows that clients will return to the illicit market if treatment is not accessible (74).…”
Section: Discussionmentioning
confidence: 76%
“…This apprehension could be reduced by making it possible to prescribe an injectable opioid substitution, within a clear legal framework, and improving the education of health professionals regarding the needs of PWIM, particularly young adults. As one study of injectable buprenorphine showed, the people most in favor of injectable treatment were those who never received prescriptions for their substance use disorder [ 23 ]. The availability of an injectable substitution would be an ideal entry point for the management of opioid use disorder and appropriate HR measures [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…As one study of injectable buprenorphine showed, the people most in favor of injectable treatment were those who never received prescriptions for their substance use disorder [ 23 ]. The availability of an injectable substitution would be an ideal entry point for the management of opioid use disorder and appropriate HR measures [ 23 , 24 ]. As young adults appear to be the most precarious people concerned, and therefore the least able to finance their care, it is necessary to facilitate their access to OST, including injectable forms, covered by the national health system [ 18 , 19 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation